POLA PERESEPAN OBAT ANTIHIPERTENSI PASIEN RUJUK BALIK (PRB) BPJS KESEHATAN DI APOTEK X JAKARTA TIMUR - Poppy, Indrianti; Chusun; Restu, Octaviani (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Hypertension is an increase in systolic blood pressure greater than or equal to (≥) 140 mmHg and/or diastolic blood pressure greater than or equal to (≥) 90 mmHg. Hypertension is one of the chronic diseases that receives services from the Referral Program (PRB). This program aims to facilitate access to health services for BPJS participants with chronic diseases. Hypertension, or high blood pressure, is one of the causes of death worldwide, with 90-95% of cases dominated by essential hypertension. This disease is considered a silent killer because people are unaware of their hypertension until they have their blood pressure checked. This study aims to determine the number and types of antihypertensive medications most frequently prescribed, identify antihypertensive medications that are and are not compliant with the National Formulary, and identify the most frequently prescribed antihypertensive drug classes for BPJS Referral Patients (PRB). This study used a quantitative descriptive method with retrospective data, namely all prescription sheets containing antihypertensive medications from October 1 to December 31, 2024. In conclusion, the results of this study indicate that hypertension patients were predominantly female (387 patients, 65.9%), and 221 patients (37.6%) were in the age group over 65 years. The most commonly prescribed antihypertensive medication was Amlodipine, with 397 prescriptions (67.6%). The most commonly prescribed antihypertensive medication class was Calcium Channel Blockers (CCBs). The compliance rate for antihypertensive medications with the National Formulary was 89.8%, while the non-compliance rate was 10.2%. This should not occur as it would impact the administrative process between pharmacies and the Social Security Administration Agency (BPJS). Therefore, ideally, 100% of antihypertensive prescriptions should be in accordance with the National Formulary.